If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2a + 10) = 5(a + 5) * 5 Reorder the terms: 6(10 + 2a) = 5(a + 5) * 5 (10 * 6 + 2a * 6) = 5(a + 5) * 5 (60 + 12a) = 5(a + 5) * 5 Reorder the terms: 60 + 12a = 5(5 + a) * 5 Reorder the terms for easier multiplication: 60 + 12a = 5 * 5(5 + a) Multiply 5 * 5 60 + 12a = 25(5 + a) 60 + 12a = (5 * 25 + a * 25) 60 + 12a = (125 + 25a) Solving 60 + 12a = 125 + 25a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-25a' to each side of the equation. 60 + 12a + -25a = 125 + 25a + -25a Combine like terms: 12a + -25a = -13a 60 + -13a = 125 + 25a + -25a Combine like terms: 25a + -25a = 0 60 + -13a = 125 + 0 60 + -13a = 125 Add '-60' to each side of the equation. 60 + -60 + -13a = 125 + -60 Combine like terms: 60 + -60 = 0 0 + -13a = 125 + -60 -13a = 125 + -60 Combine like terms: 125 + -60 = 65 -13a = 65 Divide each side by '-13'. a = -5 Simplifying a = -5
| 10h-3=70 | | w+16=8w | | 4x+4z=6 | | 9x^2=3y | | 2m^3+5m^2-18m-45=0 | | 32+5*32=192 | | 5n*n=7-n | | -4(y+3)=-6y-26 | | -4v+20=7(v-5) | | 3x(h+1)+2=20 | | x+17=-(2x-8) | | 2y^2+8y+216=0 | | -2t+4-16=-12-19t | | 9x-3(x-6)=-6 | | Y=13-5x | | -4+20=7(v-5) | | (x^2+4)((x+2)(x-2))=0 | | 9x-3(a-6)=-6 | | -2t+4-16t=-12-19t | | (x+2)(x+2)(x+2)(x-2)=0 | | 2(w+3)-5w=-24 | | 4u+6=-18 | | 5n^2-38-15n=0 | | -5w=-6w-7 | | -3t-6-2t=-6-5t | | 15x-2-6x= | | 5ln(x+1)=30 | | 2a-3a=20 | | (3X)3=24 | | (y+4)(3y-2)=-y-14 | | -2(14q-20)-4=-4(7q-9) | | 0.8-z=2.1 |